Mental health service use and barriers to help-seeking among LGBTQ+ first-year college students in Chile - Crockett, Marcelo A.; Martínez, Vania; Mac-Ginty, Scarlett; Langer, Álvaro I.; Gaete, Jorge; Núñez, Daniel; Léniz, Irene (International Journal of LGBTQ+ Youth Studies, 2025)
This study aimed to describe university students' use of mental health services and the barriers to help-seeking by sexual orientation and gender identity and to examine the factors related to these variables. A total of 7,136 first-year students from five Chilean universities participated. They answered an online survey on mental health service use, barriers to help-seeking, 12-month mental disorders, and sociodemographic variables. Data were analyzed using logistic and negative binomial regression models. Lesbian, gay, bisexual, trans, questioning, and other sexual and gender minority (LGBTQ+) students, especially trans and gender non-conforming participants, reported higher mental health service use than non-LGBTQ+ students. Sexual minority students were less likely to report the help-seeking barriers "prefer to handle on one's own" and "talk with friends/family", but were more likely to report the barriers "cost", "unsure where to go", and "time, transportation, or scheduling problems". Some variables were associated with service use and barriers in both groups (e.g. lower parental education was associated with lower service use), while others were only associated with one group (e.g. non-LGBTQ+ women reported higher service use). These results suggest that initiatives aimed at promoting access to mental health services should be tailored to different subpopulations of university students.